2016
DOI: 10.15252/embj.201695027
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor is required for optimal B‐cell proliferation

Abstract: The aryl hydrocarbon receptor (AhR), a transcription factor known for mediating xenobiotic toxicity, is expressed in B cells, which are known targets for environmental pollutants. However, it is unclear what the physiological functions of AhR in B cells are. We show here that expression of Ahr in B cells is up‐regulated upon B‐cell receptor (BCR) engagement and IL‐4 treatment. Addition of a natural ligand of AhR, FICZ, induces AhR translocation to the nucleus and transcription of the AhR target gene Cyp1a1, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 32 publications
7
55
1
Order By: Relevance
“…Emerging evidence indicates that AHR could also be activated by endogenous ligand FICZ (29). FICZ stimulates B-cell proliferation through AHR activation (48). In accordance, FICZ induces the expression of c-Jun and accelerates VSMC proliferation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Emerging evidence indicates that AHR could also be activated by endogenous ligand FICZ (29). FICZ stimulates B-cell proliferation through AHR activation (48). In accordance, FICZ induces the expression of c-Jun and accelerates VSMC proliferation.…”
Section: Discussionmentioning
confidence: 94%
“…Cells were seeded into 96-well plates and serum starved for 24 h before TCDD treatment. Cell proliferation was examined at different timepoints (24,48,72, and 96 h). Cell counting kit-8 (CCK-8) assay was performed using a CCK-8 kit (Dojindo, Kumamoto, Japan) according to the manufacturer's instructions.…”
Section: Cell Counting Kit-8 Assaymentioning
confidence: 99%
“…This difference in results might be due to the type of ligand and animal species used and the disease type examined. In addition, Villa et al (2017) demonstrated that intervention with 6-formylindolo[3,2-b]carbazole (FICZ), a natural agonist, increased AhR expression during B cell differentiation and the amount of AhR localized to the nucleus and significantly upregulated the expression of the downstream target gene CYP1A1 on B cells. These results imply that the AhR is involved in B cell proliferation and function.…”
Section: Discussionmentioning
confidence: 99%
“…Upon ligand binding, AhR is translocated into the nucleus, where AhR forms a heterodimer with AhR nuclear translocator (Arnt) and binds to dioxin response elements to induce transcription of genes involved in xenobiotic metabolism, including Cyp1a1 7 . In addition to its xenobiotic function, AhR also has endobiotic physiological functions in cell proliferation, differentiation, immune suppression, and male infertility 9 11 . AhR was recently also shown to play an important role in hepatic lipid metabolism 12 .…”
Section: Introductionmentioning
confidence: 99%